2017
DOI: 10.1161/jaha.117.006124
|View full text |Cite
|
Sign up to set email alerts
|

Cardiopulmonary Resuscitation Training Disparities in the United States

Abstract: BackgroundBystander cardiopulmonary resuscitation (CPR) is associated with increased survival from cardiac arrest, yet bystander CPR rates are low in many communities. The overall prevalence of CPR training in the United States and associated individual‐level disparities are unknown. We sought to measure the national prevalence of CPR training and hypothesized that older age and lower socioeconomic status would be independently associated with a lower likelihood of CPR training.Methods and ResultsWe administer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
81
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 99 publications
(88 citation statements)
references
References 36 publications
4
81
3
Order By: Relevance
“…Restrictions due to cost can be especially problematic in underprivileged institutions with large student bodies (and high student/teacher ratios). A previous study detected significant disparities in CPR training partially attributable to financial reasons, with lower income areas in the United States lacking in bystander CPR training [15]. In line with this, Upper Egyptian governorates like Beni-Suef are the least privileged governorates in Egypt in terms of average household income and educational attainment [16].…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Restrictions due to cost can be especially problematic in underprivileged institutions with large student bodies (and high student/teacher ratios). A previous study detected significant disparities in CPR training partially attributable to financial reasons, with lower income areas in the United States lacking in bystander CPR training [15]. In line with this, Upper Egyptian governorates like Beni-Suef are the least privileged governorates in Egypt in terms of average household income and educational attainment [16].…”
Section: Discussionmentioning
confidence: 88%
“…In line with this, Upper Egyptian governorates like Beni-Suef are the least privileged governorates in Egypt in terms of average household income and educational attainment [16]. Such financial factors may represent barriers that prevent junior doctors and medical students with relatively low incomes from receiving CPR training independently [15]. However, as this is speculative, further research regarding the barriers to CPR training in Egypt is needed.…”
Section: Discussionmentioning
confidence: 99%
“…They may also communicate more effectively with the dispatcher, which may explain the shorter response times seen in this study. A recent study revealed that highly educated individuals were more likely to be currently trained in CPR,22 which is likely to result in higher quality resuscitation. Another study has however found a negative association between education and odds of receiving bystander CPR,23 which may indicate that there is regional variation in this relationship.…”
Section: Discussionmentioning
confidence: 99%
“…Improving bystander interventions in these neighbourhoods may improve cardiac arrest survival. In a cross-sectional telephone survey, lesser education and lower income were associated with reduced likelihood of CPR training, illustrating the need to develop tailored CPR education to address this variability [23]. Language barriers for comprehension and implementation of telephone-CPR were also identified.…”
Section: Variations In Community Responsementioning
confidence: 99%